2007
DOI: 10.1016/j.juro.2007.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Vardenafil Improves Urodynamic Parameters in Men With Spinal Cord Injury: Results From a Single Dose, Pilot Study

Abstract: This trial demonstrates that in spinal cord injured patients a single 20 mg vardenafil administration achieved a significant decrease in maximum detrusor pressure, an improvement in maximum cystometric capacity and a remarkable increase in detrusor overactivity volume value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 17 publications
4
47
0
Order By: Relevance
“…PDE5-Is act mainly to relieve the dynamic and static obstruction of the prostate with a direct relaxation of the bladder [8]. Several in vitro studies have reported smooth muscle relaxation in the human bladder neck and prostate in the presence of PDE5-Is [24,25], and relaxation of the bladder neck and decreases in detrusor muscle overactivity have been detected in animal [26] and human studies [27]. Theoretically, the relaxation of the prostate and bladder neck after PDE5-I treatment could increase urinary flow; however, the concomitant relaxation of the detrusor muscle counteracts this effect, thereby preventing the observation of a final improvement in Q max [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PDE5-Is act mainly to relieve the dynamic and static obstruction of the prostate with a direct relaxation of the bladder [8]. Several in vitro studies have reported smooth muscle relaxation in the human bladder neck and prostate in the presence of PDE5-Is [24,25], and relaxation of the bladder neck and decreases in detrusor muscle overactivity have been detected in animal [26] and human studies [27]. Theoretically, the relaxation of the prostate and bladder neck after PDE5-I treatment could increase urinary flow; however, the concomitant relaxation of the detrusor muscle counteracts this effect, thereby preventing the observation of a final improvement in Q max [27].…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies have reported smooth muscle relaxation in the human bladder neck and prostate in the presence of PDE5-Is [24,25], and relaxation of the bladder neck and decreases in detrusor muscle overactivity have been detected in animal [26] and human studies [27]. Theoretically, the relaxation of the prostate and bladder neck after PDE5-I treatment could increase urinary flow; however, the concomitant relaxation of the detrusor muscle counteracts this effect, thereby preventing the observation of a final improvement in Q max [27]. However, in a urodynamic study, tadalafil at a higher dose (20 mg once daily) had no adverse effect on the bladder outlet obstruction index in men with LUTS/BPH [16].…”
Section: Discussionmentioning
confidence: 99%
“…Investigators are testing the efficacy of PDE5-selective inhibitors for reducing symptoms associated with these maladies. Symptoms of overactive bladder syndrome and urge urinary incontinence occur in both male and female patients and are related to those that occur in LUTS; inhibitors that block PDE5 and/or PDE1 activity have shown some promise in relieving symptoms and are considered potential therapies for these problems (Gacci et al, 2007). In addition, use of PDE inhibitors is being tested for treatment of premature ejaculation, Peyronie's disease, and ureteral relaxation for eased passage of kidney stones (Gratzke et al, 2007;Sandner et al, 2009).…”
Section: E Therapeutic Use Of Inhibitors Of Cgmp-hydrolyzing Phosphomentioning
confidence: 99%
“…This may be explained by the hypothesis that PDE5 inhibitors primarily affect detrusor activity rather than the BOO. 90 A study by Gacci et al 91 in men with neurogenic bladders secondary to spinal cord injury showed that vardenafil treatment resulted in significant improvements in maximum detrussor pressure, total capacity and volume triggered bladder spasms.…”
Section: Luts and Ed: Effects On Clinical Managementmentioning
confidence: 99%